Stress Analysis of Bolted Tensile end Plate Connections - Kwiatkowski, J.; Winnicki, L.A.; Krzyśpiak, A. (Engineering Transactions, 1986)
Experimental and theoretical results are presented concerning the analysis of a steel joint with a prestressing bolt Theoretical analysis is performed by means of the displacement version of the FEM. Elastic-plastic properties of the materiał are taken into account, and fictitious contact layers are used to model the friction effects and possible slips between the joint elements. Thę processes occurring in the joint during stressing and loading differ substantially from those obtained from the standard analysis based upon the simplified model of the joint.